SIKAP ORANG-ORANG KAFIR TERHADAP AJARAN ISLAM (KAJIAN HISTORY TERHADAP SURAH AL-AN’AM AYAT 7 DAN AYAT 121) - Surianto Surianto (AT-TURATS, 2018)
The persistent unbeliever will always find a reason to make moeslem cornered. As mentioned in Surah al-An’am verse 7 which declarating if wanted they have faith, so they asked the Bibel direct from the sky, in fact, if its granted, they will say that it is because or magic. Next, the inbeliever will refuted argument with what you have done. They will always find a reason to put on moeslem teaching that carried out by Prophet Muhammad SAW into cornered. Mentioned in surah al-An’’am verse 121 about the unbeliever protest that assume af dead animal aby Allan (dead it self not because of slaughteret by metioned Allah and become corpse). Its forbidden and animal dead because killed by moeslem its legimate. Then, has been explained that do not do refuted argument with them, next, moeslem commded as not to eating animal that slaughteret as not mentioned Allah because its action considered.